Evolution driven by differential dispersal within a wild bird population. - Garant, D; Kruuk, L; Wilkin, T; McCleery, R; Sheldon, B (2005)
Evolutionary theory predicts that local population divergence will depend on the balance between the diversifying effect of selection and the homogenizing effect of gene flow. However, spatial variation in the expression of genetic variation will also generate differential evolutionary responses. Furthermore, if dispersal is non-random it may actually reinforce, rather than counteract, evolutionary differentiation. Here we document the evolution of differences in body mass within a population of great tits, Parus major, inhabiting a single continuous woodland, over a 36-year period. We show that genetic variance for nestling body mass is spatially variable, that this generates different potential responses to selection, and that this diversifying effect is reinforced by non-random dispersal. Matching the patterns of variation, selection and evolution with population ecological data, we argue that the small-scale differentiation is driven by density-related differences in habitat quality affecting settlement decisions. Our data show that when gene flow is not homogeneous, evolutionary differentiation can be rapid and can occur over surprisingly small spatial scales. Our findings have important implications for questions of the scale of adaptation and speciation, and challenge the usual treatment of dispersal as a force opposing evolutionary differentiation.